2018
DOI: 10.26905/pjiap.v3i2.1921
|View full text |Cite
|
Sign up to set email alerts
|

Komitmen pemerintah daerah dalam pengembangan ekowisata di Kabupaten Sidoarjo

Abstract: The purpose of this study is to describe the commitment of local governments in developing ecotourism. The research approach uses qualitative research with descriptive types. Data obtained from observation, interviews and documentation. Determination of informants using purposive sampling. Data were analyzed using the Miles & Huberman interactive model. The results showed that Sidoarjo Regency Government (PKS) had a commitment to develop ecotourism in three dimensions. The first dimension of affective committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The legal and institutional variables (Figure 9), that most influence the sustainability of the BMC ecotourism business are the government's commitment. Rodiyah and Agustina, 2018 reported that the Sidoarjo Regency Government has gained trustworthiness and goodwill, which must be followed by consistency following the creation of the ecotourism concept. The planting of mangrove seedlings is also a manifestation of the government's continued commitment to expanding ecotourism programs.…”
Section: Results and Discussion Evaluation Of Mangrove Ecotourism Bus...mentioning
confidence: 99%
“…The legal and institutional variables (Figure 9), that most influence the sustainability of the BMC ecotourism business are the government's commitment. Rodiyah and Agustina, 2018 reported that the Sidoarjo Regency Government has gained trustworthiness and goodwill, which must be followed by consistency following the creation of the ecotourism concept. The planting of mangrove seedlings is also a manifestation of the government's continued commitment to expanding ecotourism programs.…”
Section: Results and Discussion Evaluation Of Mangrove Ecotourism Bus...mentioning
confidence: 99%
“…Studi mengenai e-service telah dilakukan oleh para peneliti terdahulu diantaranya yang membahas mengenai Aplikasi Pedulilindungi di DKI Jakarta yang dianalisis berdasarkan kualitas e-service-nya (Sherissa & Anza, 2022), M-Bonk di Kabupaten Sidoarjo yang dianalisis berdasarkan implementasinya (Choiriyah, 2020), Pelayanan Perizinan Berbasis Online di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Ciamis (Savinatunazah, 2019) yang dilihat dari efektifitasnya, serta Pelayanan Pajak Kendaraan Bermotor Secara Online di Samsat Kota Metro yang dianalisis berdasarkan implementasi pelayanannya (Daud, 2020). Adapun perbedaan dengan riset sebelumnya yaitu pada penelitian ini lokasi penelitian bukan pada instansi pemerintah melainkan pada instansi pada Badan Usaha Milik Negara dan belum pernah ada penelitian sebelumnya yang dilakukan khususnya di Plasa Telkom Garut dan yang dianalisis adalah dari sisi efektifitas pelayanannya.…”
Section: ) Pendahuluanunclassified
“…Volume semburan pada awal awal terjadinya semburan sekitar 50.000 m 2 per hari, kemudian sampai mencapai 120.000 m 3 per hari (Angraeni et al, 2014) dan kini sudah banyak mengalami penurunan. Pulau Lusi yang pengukurannya pada waktu surut memiliki luasan sekitar 94 Hektar (Prasenja, 2018) yang selama ini dikelola oleh Badan Penanggulangan Lumpur Sidoarjo (BPLS), pada Januari 2017 diserahkan pengelolaan berikut kepemilikannya kepada Kementerian Kelautan dan Perikanan (KKP) (Rodiyah & Agustina, 2018) untuk dimanfaatkan sesuai dengan tugas dan fungsi (tupoksi) nya.…”
Section: Pendahuluanunclassified